Chemokine regulation of neutrophil function in tumors. (August 2016) - Bonavita, Ornella; Massara, Matteo; Bonecchi, Raffaella
Highlights: Neutrophils are endowed with both pro- and antitumor functions. Circulating neutrophils are a heterogeneous population. Anti-tumoral (N1) neutrophils are present in early stages of tumors and metastasis while in later stages pro-tumoral (N2) neutrophils predominate. CXC chemokines binding CXCR1 and CXCR2 are abundantly produced by tumors to recruit neutrophils. After extravasation neutrophils acquire a new pattern of chemokine receptors including CCR2 that promote anti-tumoral activity. Abstract: The role of neutrophils in cancer and metastasis is still debated and controversial since they have been shown to be endowed with both pro- and antitumor functions. These contradictory results seem to be now explained by recent discoveries of tumor-associated neutrophils plasticity and multiple neutrophil subsets. Chemokines and chemokine receptors are known to tightly regulate the release of neutrophils from the bone marrow, their passage into circulation and transmigration into the tissues as well as tumor infiltration. It is emerging that chemokine receptors are differentially expressed by neutrophil subsets and they affect not only their recruitment but also their effector functions. Here we are resuming human and murine data suggesting that therapeutic modulation of neutrophil activity through the targeting of specific chemokines or chemokine receptors can improve their anti-tumoral properties.